Oil price declines and structural adjustment policies in Indonesia a static CGE analysis for 1980 and 1985 - Ezaki, Mitsuo (The Philippine Review of Business and Economics, 1989)
This paper presents a static Computable General Equilibrium (CGE) model of Indonesia constructed for 1980 and 1985, and applies the model to the analysis of comparative statics by which the impacts of oil price declines are compared between the two years and the effects of structural adjustment policies are evaluated for the two cases of financial and tax reforms in 1983. The model has been applied to the analysis of comparative statics in the case of a 10% decline in oil price for both years (1980 and 1985) independently and the results of the two years compared. A notable outcome from the comparisons is the fact that negative impacts of the 10% price decline are fairly smaller in 1985 than in 1980. This means that there should have occurred some structural changes or structural adjustments in the Indonesian economy between the two years to mitigate the negative effects of the ?reverse oil shock? which began in March 1983. Actually, two major policy reforms were introduced in 1 983 to cope with the reverse oil shock, aiming at a full mobilization of domestic resources. One was financial reform, and the other was the tax reform. Comparative statics based on the model clearly indicates that the two policy reforms, especially the financial reform, contributed significantly to the mitigation of negative effects caused by the reverse oil shock.